Evaluation of Prevalence of Patients with Chest Pain Visited in a Tertiary Care Hospital of Gujarat - Uresh J. Jain; Shah, Varsha (Asian Journal of Medical Research, 2019)
Background: Chest pain is a commonly occurring symptom affecting between 20 and 40% of the general population during their lifetime. Hence; the present study was planned for assessing the prevalence of patients with chest pain visited in hospital. Subjects and Methods: A total of 718 patients were analyzed Clinical and past medical history of all the patients was obtained. Categorization of the etiologies of all the patients with chest pain was done into following categories: Cardiovascular cause, Respiratory cause, Psychiatric cause, gastrointestinal cause, and Unknown. All the results were recorded in Microsoft excel sheet and were analyzed by SPSS software. Results: Prevalence of chest pain in the present study was 29.67 percent. Cardiovascular cause was the main reason (27.70 percent patients) for the admission of patients with chest main. Respiratory cause was the next major cause responsible for chest pain in 25.82 percent of the patients. Conclusion: Cardiovascular, respiratory and psychiatric causes are the reasons for admission of patients due to chest pain.